A new record of congrid eel, Bathycongrus bleekeri (Congridae) from Vietnam - Vo, Quang Van; Ho, Hsuan- Ching; Tran, Hoa Hong Thi; Le, Thao Thu Thi; Tran, Thinh Cong (Vietnam Journal of Marine Science and Technology, 2019)
Three specimens of Bathycongrus bleekeri were collected during the survey in 2015 and 2017. The newly recorded species is described herein, a small, moderately elongate species of Bathycongrus with head and body compressed; vertical fins without black mark; tail slender, attenuated, but not filiform; trunk length 1.2 times greater than head length; teeth small, conical, in about three-four rows on jaws, in a small triangular patch on vomer; 28–29 preanal vertebrae, total of 111–113 vertebrae; 26–28 preanal lateral-line pores. Additional data on the morphology and distribution of the species increases the total number of known species in the family Congridae in Vietnamese waters to twelve.